2012
DOI: 10.1002/hup.1263
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate, cerebral blood flow parameters, cognitive performance and mood in healthy humans: a double‐blind, placebo‐controlled, crossover investigation

Abstract: David (2012) Epigallocatechin gallate, cerebral blood flow parameters, cognitive performance and mood in healthy humans: a double-blind, placebo-controlled, crossover investigation. Human Psychopharmacology: Clinical and Experimental, 27 (2 Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(114 citation statements)
references
References 87 publications
2
110
2
Order By: Relevance
“…Antioxidants in FV may also be beneficial towards lowering inflammatory markers, which have been implicated in the onset of poor mental health including depression (29) . Although the relationship between antioxidant nutrients and psychological health is currently ambivalent, with some studies refuting the hypothesis (30)(31)(32) , a number of studies have provided evidence to support the link. For example, one CS study (29) demonstrated associations between the dietary intake of antioxidants and depressed mood in older adults, whereas another showed that concentrations of plasma carotenoids were associated with optimism (33) .…”
Section: Antioxidant Contentmentioning
confidence: 99%
“…Antioxidants in FV may also be beneficial towards lowering inflammatory markers, which have been implicated in the onset of poor mental health including depression (29) . Although the relationship between antioxidant nutrients and psychological health is currently ambivalent, with some studies refuting the hypothesis (30)(31)(32) , a number of studies have provided evidence to support the link. For example, one CS study (29) demonstrated associations between the dietary intake of antioxidants and depressed mood in older adults, whereas another showed that concentrations of plasma carotenoids were associated with optimism (33) .…”
Section: Antioxidant Contentmentioning
confidence: 99%
“…This effect appears to be dose-dependent, as the vasoconstrictive properties were only apparent at low doses (Shen et al, 2003). Wightman et al also found a reduced CBF in healthy volunteers after a single dose of 135 mg EGCG (Wightman et al, 2012). This low dose of EGCG resulted in decreased CBF in the frontal cortex during cognitive task performance (Wightman et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…Wightman et al also found a reduced CBF in healthy volunteers after a single dose of 135 mg EGCG (Wightman et al, 2012). This low dose of EGCG resulted in decreased CBF in the frontal cortex during cognitive task performance (Wightman et al, 2012). Further research is necessary to explore these dosedependent effects and underlying mechanisms.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to cocoa flavanols, there has been also interventions with the tea flavanol epigallocatechin gallate (EGCG) in young healthy volunteers reporting modulation in neuronal activity and cerebral blood flow (196)(197)(198). Furthermore, reports of MRI studies with anthocyanin-rich blueberries in both young and aged adults, revealed acute increases in CBF in specific regions of the brain, such as the occipital Table 2).…”
Section: Flavonoid-induced Changes In Cerebrovascular Function: Insigmentioning
confidence: 95%